Neurobehavioural Effects of Exposure to Fluoride in the Earliest Stages of Rat Development - Bartos, Mariana (2015)
It is known that exposure to high concentrations of Fluoride (F) produces deleterious health effects in human population. However, in the last years it has been concluded that low concentrations of F may have adverse health effects aswell. Transplacental passage of F and its incorporation into foetal tissues has been demonstrated. Therefore, the purpose of the presentwork was to study the effects of the exposure to lowlevels of F during pregnancy and lactation on the central nervous system functionality. Wistar rats were exposed to low F concentrations (5 and 10 mg/l) during pregnancy and lactation. Sensorimotor reflexes in the each pup were analysed and the postnatal day on which both eyes and auditory canals were opened was recorded. Locomotor activity and anxiety were subsequently analysed in 45- and 90-day-old offspring by an open field test and plus maze test, respectively. A significant delay in the development of eye opening was observed in all offspring whose mothers had been exposed to the two F concentrations tested. Exposure to 5 and 10 mg/l F was also found to significantly decrease locomotor activity only in 90-day-old male and female offspring. A low index of anxiety in the young females and in all adult offspring exposed to the two F concentrations tested was also detected. Taken together, findings from the present study show that exposure to low F concentrations during pregnancy and lactation produces dysfunction in the central nervous system mechanisms which regulate motor and sensitive development, locomotor activity and anxiety.